q_e-Fixed Point and q_e-Inverse Function Theorem 1D - Castillo, J. A.; Moyado, J. A. P.; Galeana, T.; Herrera, M.A.; Herrera, Israel (Discontinuity, Nonlinearity, and Complexity, 2026)
Using the definitions from [1] on the q_e-calculus we prove q_e-analogues of the Fixed Point Theorem and Inverse Function Theorem.